Low reflection and high transmission by a layered structure containing diamond-like carbon, porous silicon, and left-handed material. (March 2017) - Ubeid, Muin F.; Shabat, Mohammed M.; Altanany, Sameh M.
Abstract: In this paper, we propose and theoretically analyze a stratified waveguide structure comprised of diamond-like carbon (DLC), porous silicon (PS), and left-handed material (LHM) subjected to incident light in order to achieve low reflection and high transmission. The proposed waveguide structure is situated between two half free spaces and a TE polarized plane wave incident on it. The main parameters of each material are given and the required equations for the electromagnetic plane wave propagation are presented. Transfer matrix method is implemented to find out the characteristics of the reflected and transmitted powers. In the numerical results, the mentioned powers are computed and illustrated as a function of the incidence angle, the frequency, and the slab thickness to demonstrate the main parameters for low reflection and high transmission. These theoretical parameters could be useful to the researchers and designers working in the area of solar cells and optical sensors.